Dinamika Implementasi Kebijakan Zonasi Pada Penerimaan Peserta Didik Baru - Saidah Syakira; Resya Eka Putri; Adam Jakrinur; Muhammad Ari Khairan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This article explores the dynamics of implementing the New Student Admission (PPDB) policy, focusing on the zoning system. The study aims to analyze how this policy is carried out at the school level and the various challenges encountered during its implementation. Using a qualitative approach through observations, interviews, and document studies, the findings show that although the zoning system has succeeded in reducing the distance between students’ homes and schools, disparities in school quality remain unresolved. The affirmative pathway has not effectively reached its target groups due to limited outreach and lack of supporting facilities. Additionally, technical issues such as online system errors, address manipulation, and poor coordination between schools and education offices are significant obstacles in implementation. The study concludes that improving digital systems, enhancing human resource capacity, and actively involving communities are essential steps to ensure equitable access to and quality of education as envisioned by the policy.